Voruntersuchungen zur elektrohydraulischen Zerkleinerung von CFRP für das Carbonfaser‐Recycling. Issue 12 (20th October 2017) - Orzol, Carsten H. M.; Ohlmeyer, Martin; Krampitz, Thomas; Jäckel, H.‐Georg; Zöllner, Mareen; Lieberwirth, Holger
Abstract: The preliminary tests present that the electrohydraulic fragmentation of carbon fiber reinforced polymer (CFRP) is generally feasible and frees carbon fibers. Just like other recycling processes for carbon fibers, the demonstrated method has its advantages and disadvantages. In consideration of the test series for the composite material CFRP and its single components epoxy resin and carbon fibers, under uniform processing conditions during shock wave treatment by 1 to 500 pulse per 600 J charging energy, first research findings are gained by electrohydraulic recycling of CFRP.